Apert’s Syndrome: A Rare Case Report - Pritesh Ruparelia; Dr Tabish Mashhadi; Bharvi Shukla; Navneet Gill; Oshin Verma; Siddhi Bhojak (Journal of Orofacial Research, 2022)
Apert’s syndrome (Acrocephalo-syndactyly) is a rare congenital, autosomal dominant condition characterized by primary craniosynostosis, mid face malformations and symmetrical syndactyly of the hand and feet. Although it is inherited as an autosomal dominant trait, many cases are sporadic and present as de novo mutations arising from unaffected parents. The rarity of the syndrome and similarity of features with other craniosynostosis syndromes makes it a diagnostic dilemma. Genetic counselling and early intervention form an essential part of treatment. Because of the paucity of reported cases in Indian literature and typical features in oral cavity, a dentist should be competent to diagnose and form a part of the multidisciplinary management team. Here, we report a case of 18-year-old girl with characteristic clinical and radiographic features of Apert’s Syndrome (AS).